2021
DOI: 10.1177/0300891621996448
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of real-life data from patients with NGS panel negative and KRAS mutation positive metastatic lung adenocarcinoma

Abstract: Objective: To evaluate clinical and demographic characteristics and the results of cytotoxic treatments of KRASG12C, KRASother, and next-generation sequencing (NGS) panel negative patients. Methods: NGS data of 1264 patients with non-small cell lung cancer were retrospectively evaluated. Among these patients, the mutation distributions of 1081 patients with metastatic lung adenocarcinoma were analyzed. A total of 150 patients with negative NGS panel or mutant KRAS followed up in our clinic were included. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Another study of ICIs treating NSCLC patients with high programmed death ligand 1 (PD-L1) expression showed that the KRAS mutation status had no significant impact on the efficacy or safety of ICIs, though with a non-significant trend of worse survival in patients with KRAS G12C mutations [ 40 ]. A real-world study with 150 lung adenocarcinoma patients reported no significant difference in the PFS, OS, as well as first-line chemotherapy response among patients with or without KRAS mutations [ 41 ]. In conclusion, KRAS mutations may not have a significant impact on the prognosis of NSCLC patients.…”
Section: Kras Mutations In Cancersmentioning
confidence: 99%
“…Another study of ICIs treating NSCLC patients with high programmed death ligand 1 (PD-L1) expression showed that the KRAS mutation status had no significant impact on the efficacy or safety of ICIs, though with a non-significant trend of worse survival in patients with KRAS G12C mutations [ 40 ]. A real-world study with 150 lung adenocarcinoma patients reported no significant difference in the PFS, OS, as well as first-line chemotherapy response among patients with or without KRAS mutations [ 41 ]. In conclusion, KRAS mutations may not have a significant impact on the prognosis of NSCLC patients.…”
Section: Kras Mutations In Cancersmentioning
confidence: 99%